2020
DOI: 10.1002/ecm.1420
|View full text |Cite
|
Sign up to set email alerts
|

Testing Darwin’s naturalization conundrum based on taxonomic, phylogenetic, and functional dimensions of vascular plants

Abstract: Charles Darwin posited two alternative hypotheses to explain the success of nonnative species based on their relatedness to natives: nonnative species that are closely related to native species could experience (1) higher invasion success because of an increased probability of habitat suitability (conferred by trait similarity) or (2) lower invasion success due to biotic interference, such as competition and limiting similarity. The paradox raised by the opposing predictions of these two hypotheses has been te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 140 publications
2
24
0
1
Order By: Relevance
“…Ecological studies examining the same question or process often reach different conclusions. In invasion ecology, for example, studies have found that the phylogenetic relatedness of alien to native species can inhibit or facilitate invasion [1,2], the relationship between native and alien species richness can vary from positive to negative [3,4], and the effect of disturbance on invasion is equivocal and inconsistent [5,6]. When studies addressing the same question reach different conclusions, the different outcomes are often attributed to context dependence (see Glossary).…”
Section: The Prevalence and Problem Of Context Dependencementioning
confidence: 99%
“…Ecological studies examining the same question or process often reach different conclusions. In invasion ecology, for example, studies have found that the phylogenetic relatedness of alien to native species can inhibit or facilitate invasion [1,2], the relationship between native and alien species richness can vary from positive to negative [3,4], and the effect of disturbance on invasion is equivocal and inconsistent [5,6]. When studies addressing the same question reach different conclusions, the different outcomes are often attributed to context dependence (see Glossary).…”
Section: The Prevalence and Problem Of Context Dependencementioning
confidence: 99%
“…Many studies have investigated this conundrum across different taxonomic groups and ecosystems using observational approaches (Bezeng et al, 2015;Duncan & Williams, 2002;Park et al, 2020;Pinto-Ledezma et al, 2020;Qian et al, 2021;Strauss et al, 2006). However, the vast majority of these studies were based primarily on observations of successfully invaded exotic species, but did not consider those that were introduced but failed to establish.…”
Section: Introductionmentioning
confidence: 99%
“…While recent advances have helped disentangle this invasion paradox, relatively few studies have moved beyond species richness as the key measure of native diversity (but see work related to Darwin's naturalization conundrum; e.g. Ma et al, 2016;Marx et al, 2016;Pinto-Ledezma et al, 2020). Over-reliance on richness is a potential limitation of diversity-invasibility studies evaluating biotic resistance, as the number of native species present in a community may be a poor proxy for available niche space.…”
Section: Introductionmentioning
confidence: 99%